Endorpin Massage pada Ibu Bersalin Kala I - Tanjung, Wiwi Wardani (Universitas Aufa Royhan Di Kota Padangsidipuan, 2020)
The problem that was found was that all women who gave birth felt labor pain. Pain can cause stress which causes excessive release of hormones such as catecholamines and steroids. This hormone can cause smooth muscle tension and vasoconstriction of blood vessels. One way of non-pharmacological management is to reduce labor pain with endorphine massage. Endorphin Massage, which is a light touch and massage technique that can normalize heart rate and blood pressure as well as improve a relaxed state in the mother's body by triggering a feeling of comfort through the surface of the skin. The problem that was found was that endorphin massage had never been done on the mother at the Independent Practice Midwife (BPM) Nelly M. Harahap. Based on the results of interviews conducted with midwives, they said that they had never heard of the term endorphin massage and did not know the benefits of this action. Therefore, it is necessary to increase the competence of independent practicing midwives in an effort to reduce labor pain in laboring mothers in order to avoid unwanted complications, namely through Endorphin Massage Training. The activities carried out in this PKM are doing endorphin massage for mothers who give birth. This activity aims to reduce labor pain in mothers who give birth. The result of this activity is that there is a change in the intensity of pain felt by stage I mothers after endorphin massage.